(untitled) (Journal of Economic Research & Business Administration, 2017)
Social welfare indicators of the population include the notion of wellbeing of the individual, groups and society as a whole. In the current crisis in Kazakhstan, the practice of using precarious labour contracts is increasing in order to implement the reduction in personnel costs strategy. It actualizes the problem of the employment precarization’s impact on welfare of the majority of employees. Research is needed on distinguishing of the living conditions for standardly employed, unemployed and precariat. Important questions arise about the indicators characterizing the pattern of well-being or ill-being for these groups of people, and the method, which allows taking into account the multifactor in evaluating numerical value of well-being. The new index of social progress enables each country to assess its position in the world, to identify the most painful points in implementation of social policy.